Early Cultures of the South Anatolian Plateau, II. The Late Chalcolithic and Early Bronze Ages in the Konya Plain - Mellaart, James
I = 23:b:308; III. The Late Chalcolithic of the Konya Plain; IV. The Early Bronze Age in the Konya Plain.